Extent of eosinophilic esophagitis predicts response to treatment - Ghoz, Hassan; Stancampiano, Fernando F.; Valery, Jose R.; Nordelo, Katie; Malviya, Balkishan; Lacy, Brian E.; Francis, Dawn; DeVault, Kenneth; Bouras, Ernest; Krishna, Murli; Palmer, William C. (Endoscopy International Open, 2021)
Background and study aim The clinical impact of eosinophilic esophagitis (EoE) limited to the distal esophagus (Lim-EE) vs. diffuse involvement (Dif-EE) is unknown. This study compared clinical characteristics and outcomes of Lim-EE vs. Dif-EE.Patients and methods This retrospective, single-center study of patients with EoE between December 2011 and December 2019 evaluated treatment response based on repeated pathology and/or clinical improvement using comparative statistics.Results 479 patients were identified (126 Lim-EE, 353 Dif-EE). Lim-EE patients had a higher incidence of endoscopically identified esophagitis (23.0 % vs. 14.7 %; P = 0.04), were older (50.8 [SD 16.2] vs. 46.4 [SD 15.3] years; P = 0.007), and were more likely to present with iron deficiency anemia (5.6 % vs. 1.7 %; P = 0.05), dyspepsia (15.1 % vs. 8.8 %; P = 0.06) or for Barrett’s surveillance (10.3 % vs. 3.7 %; P = 0.02). Patients with Dif-EE presented more frequently with dysphagia (57.2 % vs. 45.2 %; P = 0.02). Both groups had similar proton pump inhibitor (87.2 % vs. 83.3 %; P = 0.37) and steroid (12.8 % vs. 21.4 %; P = 0.14) use. Patients with Lim-EE had a better clinicopathologic response (61.5 % vs. 44.8 %; P = 0.009). On multivariate analysis, EoE extent predicted treatment response with an odds ratio of 1.89 (95 % confidence interval 1.13–3.20; P = 0.02). However, treatment response based only on repeat biopsy results showed no statistical difference between Lim-EE (52.5 %) and Dif-EE (39.7 %; P = 0.15).Conclusions Lim-EE may represent a distinct phenotype separate from Dif-EE, with more overlap with gastroesophageal reflux disease and better treatment response.